1976
DOI: 10.1530/acta.0.0830243
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Half-Life of Somatomedin Activity: Evidence for Growth Hormone Dependence

Abstract: The serum half-life of somatomedin (SM) activity has been measured following the intravenous injection of SM activity into hypophysectomized rats. A [3H]thymidine incorporation assay in chick embryo fibroblasts (CEFs) has been utilized to measure SM activity. Cell cycle analysis data obtained with the flow microfluorometer shows that the [3H]thymidine incorporation data reflects actual DNA synthesis. When normal rat serum was injected, a half-life for SM activity of approximately 3 h was determined. In marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(59 citation statements)
references
References 0 publications
4
54
0
1
Order By: Relevance
“…The apparently elevated levels of IGF-I in the unextracted sera of cancer patients were clearly due to BP effects as evidenced by the detection of IGF-I binding proteins in cancer patient serum fractions having reactivity in the Amersham RIA and by the results obtained for extracted sera. The observation that serum levels of IGF-I are not increased in SCLC patients, though consistent with those of earlier reports (Minuto et al, 1986;Macaulay et al, 1988b), is perhaps surprising given the over-production of BPs in lung cancer patients and the ability of BPs to prolong the half life of IGFs in the circulation (Cohen & Nissley, 1976;Zapf et al, 1979). One explanation is that the release of IGF-I from SCLC cells in vivo is, like IGF-I release from liver, hormonally regulated by mechanisms which do not exist in vitro.…”
Section: Detection Of Immunoreactive Igf-i In Cell Conditioned Mediasupporting
confidence: 88%
“…The apparently elevated levels of IGF-I in the unextracted sera of cancer patients were clearly due to BP effects as evidenced by the detection of IGF-I binding proteins in cancer patient serum fractions having reactivity in the Amersham RIA and by the results obtained for extracted sera. The observation that serum levels of IGF-I are not increased in SCLC patients, though consistent with those of earlier reports (Minuto et al, 1986;Macaulay et al, 1988b), is perhaps surprising given the over-production of BPs in lung cancer patients and the ability of BPs to prolong the half life of IGFs in the circulation (Cohen & Nissley, 1976;Zapf et al, 1979). One explanation is that the release of IGF-I from SCLC cells in vivo is, like IGF-I release from liver, hormonally regulated by mechanisms which do not exist in vitro.…”
Section: Detection Of Immunoreactive Igf-i In Cell Conditioned Mediasupporting
confidence: 88%
“…This is not unexpected since the three traits are interrelated and a linear correlation has been reported between the sum of concentrations of IGF-I and IGF-II, and IGFBP-3 (21). Classically serum IGFBP-3 levels are known to vary according to growth hormone secretion (24). Other factors influencing the circulating IGFBP-3 level include age, pubertal development, nutrition, and hepatic function (21).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the IGF-I levels in normal synovial fluid were about one-tenth of those in normal adult human serum, reported to be 176 ± 49 ng/ml [6] and that IGF-I levels in synovial fluid from patients with RA were much higher than those in normal samples, suggesting that local regulation of IGF-I may occur in synovial fluid. IGFBP-3 is known to be the most abundant IGFBP in serum, forming a ternary complex (150 kDa), that serves as the major circulating carrier of the IGFs and increases the half-life of the IGFs in the circulation [7]. In contrast to serum, the 42-39 kDa doublet (IGFBP-3) was low in normal synovial fluid, and a prominent immunoreactive 30 kDa IGFBP-3 fragment was detected by Western immunoblot analysis.…”
Section: Discussionmentioning
confidence: 99%